Ethyl 2-(5-methyl-1,2,4-triazolo[1,5-a]pyrimidin-7-yl)pent-4-enoate - Sanae Lahmidi; Mohamed El Hafi; Ahmed Moussaif; Mohammed Benchidmi; El Mokhtar Essassi; Joel T. Mague (IUCrData, 2018)
In the title molecule, C13H16N4O2, the fused triazolopyrimidine ring system is planar. In the crystal, inversion-related C—H...O hydrogen bonds form dimers that are linked into chains extending along the a-axis direction by inversion-related C—H...π(ring) interactions.